PEMEROLEHAN SINTAKSIS BAHASA INDONESIA ANAK USIA DUA TAHUN DAN TIGA TAHUN DI PADANG BULAN - Ismarini Hutabarat (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
This research found that generally two-year-old and three-year-old children could produce sentences in all moods in their daily conversations. But in the research it was found that there was a subject of two-year of age who could only produce sentences in declarative and imperative moods. It was also found that three-year-old children could improvise the sentences they produce. Sometimes, two-year-old children imitated what other people said when they had difficulties to express something, but three-year-old children had already had good competence in producing sentences of their own creations. The syntax acquisition of two-year-old and three-year-old children were affected by four factors which were natural factor, cognitive development factor, social background factor and heredity factor; intelligence and the style of language acquisition.